Thermal Conductivity Behaviour of Silicon Carbide Fiber/Phenolic Resin Composites by the Introduction of Graphene Nanoplatelets - Kim, Tae-Eon; Chul Bae, Jin; Youn Cho, Kwang; Shul, Yong-Gun; Hyung Riu, Doh (Asian Journal of Chemistry, 2013)
Silicon carbide (SiC) represents many unique properties, such as high strength, corrosion resistance, high thermal conductivity and high temperature stability. In recent years, the SiC fibers have been widely studied for use as a fillers in polymer-matrix composite materials due to these characteristics. In order to improve the properties of such polymer-matrix composite materials dramatically, the use of graphene as an additive has been investigated both academically and industrially, as it can induce synergetic effect in the polymer-matrix composite materials, including thermoplastic and thermoset composite. In this study, we fabricated highly thermally conductive composites using Tyranno®-SA3 SiC fibers and a phenolic resin. Graphene nanoplatelets were added to composites to improve their thermal conduction properties. Thermal conductivity measurements indicated that in case of the graphene-free composites, thermal conductivity was the highest (4.1 W/m·K) when the filler was added in an amount of 50 vol %, due to the resulting structure formed by filler and matrix being closed-packed. The thermal conductivity and thermal diffusivity measurements of the graphene-nanoplatelets-containing composites showed that addition of the graphene nanoplatelets increased the thermal conductivity values of the composites. In case of the composite containing 50 vol % filler, the thermal conductivity increased to 5.5 W/m·K. This increase was due to a synergetic effect between the SiC filler and the binder induced by the graphene nanoplatelets.